India: Introduction. - Dalrymple, William (New Statesman, 2006)
Part of a special section on India. India is poised to overtake Japan as the third largest economy in the world, but the Indian caste system has ensured that the country's rapid development is being driven by an elite minority. In Hyderabad, for example, computer programmers have claimed large chunks the U.S. software writing market; at the same time, 50 miles to the north, farmers have been poisoning themselves in debt-related mass suicides. Amid its economic boom, the subcontinent remains as unpredictable as ever.